SOLITARY JEJUNAL METASTASIS FROM RENAL CELL CARCINOMA - Bahli, Zahid M; Panesar, K J (Journal of Ayub Medical College Abbottabad, 2007)
A metastatic deposit from renal cell carcinoma into the jejunal wall is a rare phenomenon. Among the frequent modes of presentation, bleeding, obstruction and unexplained anaemia are commonly seen. In addition to the conventional contrast studies and computerized tomography (CT), Capsule endoscopy is a useful diagnostic tool. Factors responsible for resistant behaviour of jejunal wall are still not clear, however when it happens it is really a diagnostic challenge. We are reporting this rare case of solitary jejunal metastasis from renal cell carcinoma. Keyword: Jejunum; Metastasis ; Renal; Carcinoma